2022
DOI: 10.1186/s12891-022-05852-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of transport gap bending deformity in the treatment of critical-size bone defect after bone transport

Abstract: Background The purpose of this study was to investigate the risk factors of transport gap bending deformity (TGBD) in the treatment of critical-size bone defect (CSBD) after the removal of the external fixator. Methods From January 2008 to December 2019, 178 patients with bone defects of the lower extremity caused by infection were treated by bone transport using a unilateral external fixator in our medical institution. TGBD was defined as the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In our study, the univariate and multivariate logistic regression analysis showed that gender, height, defect site, and external fixation index (EFI) were important risk factors for axial deviation. Multiple studies have examined the association between gender, defect site, and EFI with axial deviation, reporting various findings [ 7 , 24 , 25 ]. Firstly, the gender factor potentially exerts a certain degree of influence on axial deviation during bone transport procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the univariate and multivariate logistic regression analysis showed that gender, height, defect site, and external fixation index (EFI) were important risk factors for axial deviation. Multiple studies have examined the association between gender, defect site, and EFI with axial deviation, reporting various findings [ 7 , 24 , 25 ]. Firstly, the gender factor potentially exerts a certain degree of influence on axial deviation during bone transport procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Before the advent of the induced membrane technique, bone reconstructions were centered around the use of a vascularized fibula graft [17][18][19][20][21] and bone transfer according to Ilizarov. [22][23][24] These surgeries are technically difficult, the results random [25][26][27] and less well tolerated in the pediatric population in relation with wearing an external fixator for a long period of time. 7,8 Although being one of the reference solutions, the original Masquelet's technique in young children is limited by the small volume of the iliac crests, constituting an insufficient supply of autologous cancellous bone graft to fill the important bone losses, resulting in a longer bone regeneration and fragility.…”
Section: Discussionmentioning
confidence: 99%